HALAL TOURS AS THE FORM OF ISLAMIC CIVILIZATION PROGRES: - Maulidi, Mohammad Jeffry (Hunafa: Jurnal Studia Islamika, 2018)
This research found that implementation of da’wah in Halal tourism in Special Economic Zones (KEK) in multicultural on the application of Islamic cultural values through social construction and approach of education Sunnah can improve progress and contribution to society and quality of facilitation of educational development to increase understanding source of human power. This research is a field research with qualitative method used with history and sociological approach. Data collection techniques are done by interviews, observations, and documents. A source of data in this study is the community of tourism actors in the Special Economic Zone of Lombok. This research produces and enhances the application of Islamic cultural values to the improvement of Human Resources and preservation of existing local wisdom, in the Special Economic Zones (KEK) is a pro-business policy from the government in order to accelerate the achievement of national economic development, which aims to accelerate regional development.